KAJIAN REPARASI LAMBUNG KAPAL TONGKANG SML 05 DENGAN METODE SANDBLASTING DAN PAINTING - Amjad Mulkus Fadlurrohman; Pratama Yuli Arianto; Rudianto . (Jurusan Teknik Mesin, 2023)
The shipping industry is one of the future industries that has a major role in development because it can grow other maritime sectors to create new economic growth. Based on this, a study of hull repair is needed to support related industries. Hull repair cannot be separated from the sandblasting and painting processes. Sandblasting and painting are modern methods that aim to protect the hull from damage that can affect the life of the ship. The advantage obtained when the sandblasting and painting process meets the standards is that the repair results are more optimal to minimize shipyard expanses. In this study, the sandblasting process has followed the standards both at each stage and the calculation of estimated material requirements on the flat bottom, vertical side underwater, and topside position. In the painting study, the flat bottom and vertical side underwater position met the minimum requirements for paint, while the top side had a shortfall compared to the calculation of the estimated requirement of 8.8 liters.